KEBANGKITAN KEMBALI GERAKAN KELOMPOK TERLARANG GAFATAR DI KOTA PALOPO SULAWESI SELATAN - Sitti Arafah; Sabara; Ahmad Aridllah Rahman (Balai Penelitian dan Pengembangan Agama Jakarta, 2023)
This article delves into the resurgence of a banned group, Gafatar, in Palopo City. The group was officially banned by the government in 2016. The resurgence of this movement was known to the public when a video featuring the pledge of allegiance or baiat by three religious college students in Palopo City on November 9, 2020, went viral. The research employed a fact-finding method to uncover the details and underlying issues surrounding this pledge of allegiance. The research primarily focuses on establishing the timeline of events related to the pledge and identifying the religious group responsible for the incident. This study found the involvement of the ex-Gafatar group in the video, as the figures have beliefs and teachings similar to those of the group. This indicates that, despite being banned, the Gafatar group remains active in disseminating its beliefs and recruiting new members. The resurgence of Gafatar's activities poses a significant risk of triggering socio-religious issues within society, necessitating swift responses from relevant authorities.